Serum magnesium level in eclampsia at tertiary care center, Gujarat, India - Patel, Nidhi; Shah, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Magnesium may be physiologically important in blood pressure regulation whereas changes in magnesium levels could contribute to the patho-etiology of hypertension. The objective of the present study was to study the level and effect of magnesium in eclamptic pregnant women. Methods: This cross-sectional study was conducted among 50 clinically diagnosed women with eclampsia in their third trimester of pregnancy. Inclusion criteria for the study was; females with singleton pregnancy, all in the third trimester which were diagnosed to have PIH based on the development of hypertension for the first time, proteinuria with or without edema, with no history of previous urinary tract troubles and no evidence of UTI. The concentration of total serum magnesium was measured by atomic absorption spectroscopy. Results: Mean age, mean gestational age, mean total hospital stays, mean BMI, mean systolic BP and diastolic BP was 24.3 years with 5.1 SD, 36.4 week with 3.3 SD, 7.8 days with 2.4 SD, 28.9 wt/ht2 with 4.8 SD, 146.5 mmHg with 14.7 SD and 95.9 mmHg with 11.2 SD respectively. Mean magnesium level was 1.9 mmol/L with 2.2 SD. Conclusions: Hypomagnesemia is present in eclamptic pregnant women. In developing countries like India, sufficient dietary supplementation should be given above the recommended dietary allowances in pregnancy at least in susceptible pregnant women.